C-glycosides of dodecanoic acid: new capping/reducing agents for glyconanoparticle synthesis - Ramana, C. V.; Durugkar, Kulbhushan A.; Puranik, Vedavati G.; Narute, Sachin B.; Bhagavatula L. V. Prasad (Tetrahedron Letters, 2008)
A concise synthesis of 12-C-glycosylated dodecanoic acids employing an olefin cross-metathesis reaction is developed. Examination of these acids as capping agents for the synthesis of metal nanoparticles reveals that they do not cap the Co-metal nanoparticles synthesized in aqueous phase, but that two of them can reduce and cap the Ag nanoparticles in water without any aggregation. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: C-Glycosides; Cross metathesis; glyconanoparticles; Grubbs' catalyst; silver nanoparticles

Stereospecific synthesis of C-arabinofuranosides and carba-disaccharide analogues of Motif C of cell wall AG complex of Mtb - Patil, Rahul S.; Ahire, Ketan M.; Ramana, C. V. (Tetrahedron Letters, 2012)
A simple strategy for the synthesis of alpha- and beta-C-arabinofuranosides featuring a furan ring transposition reaction has been developed. A novel double furan ring transposition reaction has proposed and executed for the synthesis of the carba-disaccharide analogue of Motif C of the cell wall AG complex of Mtb. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Arabinose; C-Glycosides; Carba-disaccharide; Cell wall AG complex; Ring transposition